A pulsed high-voltage decelerator system to deliver low-energy antiprotons - Husson, Audric; Kim, B. H.; Welker, A.; Charlton, M.; Choi, J. J.; Chung, M.; Clade, P.; Comini, P.; Crepin, P. -P.; Crivelli, P.; Dalkarov, O.; Debu, P.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2021)
The GBAR (Gravitational Behavior of Antihydrogen at Rest) experiment at CERN requires efficient deceleration of 100 keV antiprotons provided by the new ELENA synchrotron ring to synthesize antihydrogen. This is accomplished using electrostatic deceleration optics and a drift tube that is designed to switch from -99 kV to ground when the antiproton bunch is inside – essentially a charged particle “elevator” – producing a 1 keV pulse. We describe the simulation, design, construction and successful testing of the decelerator device at -92 kV on-line with antiprotons from ELENA.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Antihydrogen; Charged-particle optics; General Relativity; Ion-optic simulations